Theft and Reception of Host Cell's Sialic Acid: Dynamics of Trypanosoma Cruzi Trans-sialidases and Mucin-Like Molecules on Chagas' Disease Immunomodulation - Fonseca, Leonardo Marques da; da Costa, Kelli Monteiro; Chaves, Victoria de Sousa; Freire-de-Lima, Célio Geraldo; Morrot, Alexandre; Mendonça-Previato, Lucia; Previato, Jose Osvaldo; Freire-de-Lima, Leonardo (Frontiers in Immunology, 2019)
The last decades have produced a plethora of evidence on the role of glycans from cell adhesion to signaling pathways. Much of that information pertains to their role on the immune system and their importance on the surface of many human pathogens. A clear example is the flagellated protozoan Trypanosoma cruzi that display in its surface, including the O-linked mucin-like glycoproteins, as well as glycan-binding proteins belonging to the trans-sialidase (TS) family, which present active (aTS) and inactive (iTS) members. Over the last thirty years, it has been well described that T. cruzi is unable to synthetize sialic acid (SIA) on its own, making use of aTS to steal the host’s SIA. Although iTS did not show enzymatic activity, it retains a substrate specificity similar to aTS (α-2,3 SIA-containing epitopes), displaying lectinic properties. It is accepted that aTS acts as virulence factor in acutely T. cruzi infected hosts. However, recent findings have demonstrated that iTS may also play a pathogenic role during T. cruzi infection, since it modulates events related to adhesion and invasion of the parasite into the host cells. However, since both TS proteins share structural substrate specificity, following T. cruzi infection, it might be plausible to speculate if iTS may be able to assuage and/or attenuate biological phenomena depend on the catalytic activity displayed by enzymatically active members. Since SIA-containing epitopes modulate in the host immune system, it should not come as any surprise that changes in the sialylation of parasite’s mucin-like molecules, as well as host cell glycoconjugates might disrupt critical physiological events, such as the building of effective immune responses. This review aims to discuss the importance of mucin-like glycoproteins and TS molecules for T. cruzi biology, as well as present a snapshot of how disturbances in both parasite and host cell sialoglycophenotypes may facilitate the persistence of T. cruzi in their infected host.